Clinical pharmacokinetic interactions between antiepileptic drugs and hormonal contraceptives - Reddy, Doodipala Samba (2010)
Contraceptive management in women with epilepsy is critical owing to the potential maternal and fetal risks if contraception or seizure management fails. This article briefly describes the pharmacokinetic interactions between antiepileptic drugs (AEDs) and hormonal contraceptives and the rational strategies that may overcome these risks. Hormonal contraception, including the use of oral contraceptives (OCs), is widely used in many women with epilepsy – there is no strong evidence of seizures worsening with their use. AEDs are the mainstay for seizure control in women with epilepsy. However, there are many factors to consider in the choice of AED therapy and hormonal contraception, since some AEDs can reduce the efficacy of OCs owing to pharmacokinetic interactions. Estrogens and progestogens are metabolized by cytochrome P450 3A4. AEDs, such as phenytoin, phenobarbital, carbamazepine, felbamate, topiramate, oxcarbazepine and primidone, induce cytochrome P450 3A4, leading to enhanced metabolism of either or both the estrogenic and progestogenic component of OCs, thereby reducing their efficacy in preventing pregnancy. OCs can also decrease the concentrations of AEDs such as lamotrigine and, thereby, increase the risk of seizures. Increased awareness of AED interactions may help optimize seizure therapy in women with epilepsy.